Hydrothermal treatment of Tartary buckwheat grain hinders the transformation of rutin to quercetin. (November 2016) - Lukšič, Lea; Árvay, Július; Vollmannová, Alena; Tóth, Tomás; Škrabanja, Vida; Trček, Janja; Germ, Mateja; Kreft, Ivan
Abstract: The impact of hydrothermal treatment on extractability of flavonoids from starchy matrix was investigated. Tartary buckwheat grain was hydrothermally treated (HT) and milled to yield HT flour. In not hydrothermally treated (NHT) Tartary buckwheat flour, most of extractable rutin (8 mg of rutin per g DM (dry matter)) was extracted during the first 20 min of extraction. In contrast, in HT Tartary buckwheat flour only 4 mg of rutin per g DM was extracted in 20 min, and 6 mg and 7 mg of rutin per g DM within 2 and 8 h, respectively. This indicates that, during the hydrothermal treatment, rutin becomes embedded in the flour matrix, becoming less readily extractable. Slowly extracted rutin was protected from transformation to quercetin during dough and bread making. Thus, from an initial 7 mg of extractable rutin per g DM in HT buckwheat flour, the resulting Tartary buckwheat bread contained 2 mg of rutin per g DM, and 6 mg of quercetin per g DM appeared. No other Tartary bread making technology which would be able to conserve such an amount of rutin from flour through the process to the final bread product is known to our knowledge. Highlights: Impact of hydrothermal treatment on extractability of flavonoids was studied. Extraction of rutin was delayed by hydrothermal treatment of grain. During bread making 26% of rutin was protected from transformation to quercetin. This is the only known buckwheat bread-making technology conserving rutin in bread.